Motor features, dermatoglyphic and EEG periods of girls in pre and post menarche - Letícia Ecard Rocha; Paula Roquetti Fernandes; José Fernandes Filho (University of Banja Luka, Faculty of physical education and sport, 2013)
The identification of menarche at puberty is important to evaluate the physical qualities, since the organism is developing a result of maturation. The dermatoglyphic characteristics are presented as possible indicators of genetic predispositions for basic physical qualities such as strength, speed, endurance, power and coordination. The aim of this study is relation of motor characteristics, dermatoglyphic and brain electro in girls in the periods before and after menarche. For this purpose the sample consisted of 45 girls aged between 10 and 14 years and 11 months divided into two groups, 21 in pre-menarche group (G1) and 24 in post menarche (G2). The variables analyzed were: motor characteristics, dermatoglyphic and EEG (absolute power in alpha and beta) electrodes in the frontal regions (F), central (C) and parietal (P), using the protocol KTK, protocol and capture fingerprints spectral activity through EEG. The results show a significant difference in QM4 for a p≤.05 between groups G1 and G2, and the G2 achieved better performance. Compared the results of the motor characteristics, dermatoglyphic and electroencephalographic they indicate significant differences in spectral activity of the alpha rhythm in girls belonging to the group after menarche. It was observed that, with respect to motor characteristics, dermatoglyphic and EEG, the groups are not presented separately. However, to join the motor characteristics, dermatoglyphic and EEG groups before and after menarche, there was a significant difference with respect to brain activity only in the alpha rhythm and at frontal (F3, FZ, F4) and central (C3 and CZ) and in the post menarche.